Cost estimates of COVID-19 clinical management in Myanmar - Phyu Win Thant; Khin Thu Htet; Wit Ye Win; Ye Min Htwe; Thant Sin Htoo (BMC, 2021)
Abstract Objective This study aims to estimate the cost of clinical management of COVID-19 infected patients based on their severity by exploring the resources used in health care provision in Myanmar. Methods A multicenter retrospective cost analysis of COVID-19 patients was performed using the micro-costing approach from the perspective of the health system. It covered two cost components, namely direct and indirect cost of treating a patient. Input data and their quantities were obtained from COVID-19 Standard Treatment Guidelines of Ministry of Health and Sports, and administrative and financial records of resource utilization of three designated health facilities in Yangon Region. Valuation of these resources was based on the price list from the Procurement Section of the Ministry. Results This study estimated the unit cost of clinical management of COVID-19 infected patients with no symptom to be 953,552 MMK(717 USD), with mild-moderate symptoms to be 1,155,222 MMK(869 USD) and with severe-critically ill conditions to be 5,705,052 MMK(4290 USD). Average cost for a patient par day was 86,687 MMK(65 USD) for asymptomatic patients, 105,020 MMK(79 USD) for mild-moderate patients and 283,252 MMK(214 USD) for severe-critically ill patients. Since the first case detected till December 31, 2020, COVID-19 clinical management cost was accounted for 139 Billion MMK (104 Million USD) for total 124,630 confirmed cases. Conclusions COVID-19 pandemic has caused health systems to incur the significant health care expenses. Timely implementation of the sustainable, affordable and efficient policy for COVID-19 responses is of utmost important for every nation especially in the face of a pandemic. This study provides the fundamental inputs for strategic planning, for future economic evaluations of different policy interventions, and policy recommendations for health systems to remain resilient during and after the COVID-19 pandemic in Myanmar.